Biomass gasification process with the tar removal technologies utilizing bio-oil scrubber and char bed. (15th May 2016) - Nakamura, Shunsuke; Kitano, Shigeru; Yoshikawa, Kunio
Highlights: Primary tar removal methods were developed for biomass gasification. Utilization of byproducts for tar removal was investigated. The bio-oil scrubber and the char bed filter are effective for low-cost tar removal. 98% of tar was eliminated by the combination of some secondary methods. Abstract: We develop tar removal technologies by using byproducts (bio-oil and char) in order to achieve low-cost and highly effective tar removal using only secondary removal methods in a pilot-scale gasification facility. The tar removal performance of a 100-L bio-oil scrubber and a 13-kg char filter is investigated with an up-draft gasifier. The tar removal rate of the bio-oil scrubber at 40, 50, and 60 °C is measured; the highest removal rate is 64.5% at 50 °C. Furthermore, even though the tar removal performance of water/oily scrubber generally degrades, that of the bio-oil scrubber does not decrease even after use for 22.5 h. The char can also be used as a tar adsorbent, like activated carbon, because of its high porosity. The char bed filter removes 81.5% of the tar from the producer gas at the beginning of the operation. The entire tar removal system, including the bio-oil scrubber and the char bed filter, exhibits a 98% tar removal rate.